Ipoteza= triungiul M N P
m(M)= 2 x m(N)+3
m(P)=3 x m(N)+9
Concluzie: m(M)=?
m(N)=?
m(P)=?
Răspunsuri la întrebare
Răspuns de
1
Rezolvare :
m(M) + m(P) + m(N) = 180 (grade)
↓ ↓
2×m(N)+3 + 3 ×m(N) +9 + m(N) = 180
2N + 3 + 3N + 9 + N = 180
6N +12 = 180
6N = 168 ⇒ N= 168/6 ⇒N = 28
⇒ m(N) = 28 grade
M = 2N + 3 =2×28 +3 = 56+3 = 59
⇒ m(M) = 59 grade
P= 3N + 9 =3×28 +9 = 84+9= 93
⇒ m(P) = 93 grade
m(M) + m(P) + m(N) = 180 (grade)
↓ ↓
2×m(N)+3 + 3 ×m(N) +9 + m(N) = 180
2N + 3 + 3N + 9 + N = 180
6N +12 = 180
6N = 168 ⇒ N= 168/6 ⇒N = 28
⇒ m(N) = 28 grade
M = 2N + 3 =2×28 +3 = 56+3 = 59
⇒ m(M) = 59 grade
P= 3N + 9 =3×28 +9 = 84+9= 93
⇒ m(P) = 93 grade
Alte întrebări interesante
Informatică,
9 ani în urmă
Matematică,
9 ani în urmă
Studii sociale,
10 ani în urmă
Limba română,
10 ani în urmă
Limba română,
10 ani în urmă
Limba română,
10 ani în urmă